Uma proposta de ensino de ondas sonoras em ambiente virtual e real - CORRÊA, Rosiane Barata (2022)
The contents presented in the classroom do not always arouse the interest and attention of the student. Physics teaching, like any other science, requires methodological strategies that seek to interconnect the student's sociocultural context with the theoretical concepts studied, so that, thus, arouse their curiosity and promote the construction of new knowledge. In addition provide a more pleasurable teaching. In this sense, this work aims to develop a methodological proposal for teaching sound waves in a virtual and real environment that is more attractive and interesting for student learning. For that, foundations were sought in recent theoretical references, in order to contextualize the research theme. Regarding the methodological procedures, a didactic sequence (DS) based on the three pedagogical moments (3PM) was elaborated, addressing the content of sound waves (sound) and noise pollution through the technological tool of the Smartphone and App Sound Meter, which works as a decibel meter to calculate in decibel units the sound intensity level of certain environments, making it possible to carry out an investigative activity to be adopted by teachers and students to facilitate the teaching-learning process. Also, make them aware of the consequences caused due to noise pollution related to human health.